The Effect of Femoroacetabular Deformity on Lower-Limb Joint Biomechanics During Daily Functional Tasks - Dwyer, Kevin (Université d'Ottawa / University of Ottawa, 2014)
Femoroacetabular impingement (FAI) is a hip joint deformity that causes joint pain, decreases joint range of motion and results in abnormal kinematic and kinetic characteristics. It is not known whether these biomechanical variations are caused by the actual mechanical impingement aspect of hip deformity or neuromuscular adaptations and soft tissue damage associated with pain. The purpose of this study was to investigate the effects of femoroacetabular cam deformity (FAD) during daily functional tasks. This was accomplished by measuring and comparing the hip joint biomechanics of symptomatic FAI (sFAI), asymptomatic FAD, and control (CON) subjects. Fifty one subjects volunteered to the study (n = 51; CON = 17, FAD = 18, sFAI = 16) and they performed 6 simulated activities of daily living: stair ascent and descent, sit-to-stand and stand-to-sit, dynamic range of motion, maximum depth squats and level walking tasks while motion ground reaction force and muscle activity were recorded. However, only the squat and level walking tasks were analyzed for this thesis. For each task, three-dimensional kinematics and kinetics were recorded and analyzed. Qualitative questionnaires (HOOS and WOMAC) and physical exams were also part of the testing protocol, and maximum voluntary isometric contractions (MVIC) were collected as part of a separate EMG protocol. The EMG results were not analyzed but the MVIC results were and the moments of force were determined. The sFAI group had significantly reduced scores for all HOOS and WOMAC metrics compared to FAD and CON. The sFAI group had significantly reduced external rotation, internal rotation, and a trend indicating reduced hip flexion compared to FAD and CON groups. The FAD group had a trend indicating reduced internal rotation compared to CON. There were no differences in the moments of force between groups for the MVICs. No statistically significant differences were observed between groups for the squat trials, however, the sFAI group showed biomechanical variations. Both the CON and FAD groups were able to squat deeper, had greater pelvic range of motion and a larger maximum hip and knee flexion angle compared to sFAI. Similarly, the walking tasks did not elucidate any between group differences in biomechanical characteristics. Yet, there was a noticeable trend of decreased peak hip abduction angle in the sFAI group compared to CON. This result may be indicative of a gait adaptation based on the pain that sFAI subjects endure over a long period of time. Interestingly, the FAD group did not have obvious gait patterns similar to either the CON or sFAI, making it unclear if the asymptomatic cam deformity has any gait adaptation effects. Since no differences were observed between FAD and CON in squatting and walking, the actual bone deformity may not be the cause of restricted motion during daily activities as previously thought. Internal rotation physical examination appears to indicate potential restrictions in the FAD compared to CON, and may be the best parameter to assess differences between groups and predict the presence of cam deformity. It is suggested that the presence of pain, caused by soft tissue damage over time, may be confounding factors leading to the biomechanical and neuromuscular discrepancies observed in sFAI, and should be the next avenue of study.
Keywords: FAI; Impingement; Hip Biomechanics; Squat; Femoroacetabular Impingement; Gait